Comparative studies on C-coated and uncoated LiFePO4 cycling at various rates and temperatures using synchrotron based in situ X-ray diffraction - Shin, Ho Chul; Nam, Kyung Wan; Chang, Won Young; Cho, Byung Won; Yoon, Won-Sub; Yang, Xiao-Qing; Chung, Kyung Yoon (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
The structural changes of LiFePO4 and C-coated LiFePO4 during charging at various C-rates and temperatures are investigated using synchrotron based in situ X-ray diffraction technique. The XRD patterns collected during cycling show the structural evidence of the positive effects of carbon coating on LiFePO4 for the electrochemical performance improvements at different temperatures, especially at low temperatures. At -10 degrees C, the C-coated LiFePO4 shows comparable capacities with the sample cycled at room temperature when cycled at C/5 rate with a slight shift of the plateau to a higher voltage during charging. The in situ XRD patterns collected simultaneously show a complete phase transformation from triphylite to heterosite. At -20 degrees C, the C-coated LiFePO4 delivers 55.6% of its theoretical capacities at C/5 rate. However, the plateau in the charging curve becomes sloppy and shifts to a higher voltage. The in situ XRD patterns show that the phase transformation from triphylite to heterosite is not completed when charged to 4.5 V due to the larger polarization when charged at -20 degrees C. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: LITHIUM BATTERIES; PHOSPHO-OLIVINES; ELECTRODES; SPECTROSCOPY; ABSORPTION; LIXFEPO4